Sosialisasi Pengolahan Sampah Organik dan Anorganik Menggunakan Media Pembelajaran pada Siswa Sekolah Dasar - Azza Feridyan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This service aims to implement a socialization program for processing organic and inorganic waste using learning media for elementary school students. Through active involvement in media-based learning activities, students are given a deeper understanding of the importance of waste management for the environment. This method is designed to increase ecological awareness and motivate active participation in environmental conservation efforts from an early age. The results of this program show an increase in students' understanding over time, as well as engaging them in simple waste management practices at school and home. It is hoped that this outreach can become the basis for forming sustainable behaviour in the younger generation, creating positive changes in their actions towards the environment.